Patrimoine(s) et Conservation-Restauration(s) - Roland May (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Evolution and expansion of a cultural heritage concept applied to fields such as contemporary art and, sciences, technology, ethnography...over the last twenty five years, raises questions about its relationship with conservation, the bases of which were defined in the sixty's, then essentially focused on artwork and aestheticism.With respect to other values and stakes, messages, functions, use, isn't it the opportunity to assess the suitability of these notions and, to some extent, their integration in a process which preserves the narrow and compulsory link between conservation and the durability of cultural heritage with respect to both ancient and new values?